A STUDY OF ACADEMIC PERFORMANCE IN RELATION TO MATHEMATICAL ANXIETY AMONG SECONDARY SCHOOL STUDENTS - GEETA SHARMA (Innovative Research Thoughts, 2021)
The goal of the current investigation was to investigate the relation between academic performance and mathematical anxiety among secondary school students. A random sample of one hundred students from a secondary school in Sonipat, located in Sonipat district in the state of Haryana, participated in this research. The findings of the research indicate that There is a negative relationship between mathematical anxiety and academic performance.